TikTok Users among University Students in Sarawak, Malaysia - Parveen, Kaur; Arif, Jawaid; Imelda Ulau, Bilong; Pui, Siao Wei; Sivashunmugam, Sangaran (Journal of Hunan University Natural Sciences, 2023)
TikTok is a video-sharing application that allows its users to record short video clips. The popularity of this application has shown a drastic growth over the past decade. It has proven to be one of the most downloaded applications in various statistics. This research aims to analyze public opinion toward TikTok and the factors and implications of getting involved with this video-sharing application. Based on user-centric theory, it focuses on user experiences, needs, and goals. User-centered design uses interactive design to enhance the relationship between users and technology applications. In addition, user experience theory can represent the emotions of users who use the application. The sample consisted of 100 students studying at the University Malaysia Sarawak, who were randomly selected and completed the questionnaire that we had on Google Forms. The data were analyzed using descriptive analysis and Spearman correlation. The study also indicates that some of the short videos contain inappropriate elements and profane language that can create rumors in society. However, the result also reveals that using the TikTok application can sharpen their skills in making videos and help them reduce their stress. Moreover, the results of the Spearman correlation showed a significantly high positive correlation between the interesting content of the TikTok short videos and the use of TikTok. This study illustrates several recommendations, which can hopefully improve the quality of the videos and reduce the number of inappropriate elements.